A Comparison of Dental Treatment Utilization and Costs by HMO Members Living in Fluoridated and Nonfluoridated Areas - Gerardo Maupomé, BDS, MSc, PhD; Christina M. Gullion, PhD; Dawn Peters, PhD; (Blackwell Synergy, 2007)
To compare dental treatment experiences and costs in members of a health maintenance organization (HMO) in areas with and without community water fluoridation.